NYAI DALAM MODERNISASI PESANTREN PUTRI (Studi Kasus di Pesantren Mambaul Ulum Pamekasan) - Kulsum, Ummu (JURNAL TADRIS STAIN PAMEKASAN, 2010)
Abstract: This article will examine the efforts undertaken innovation Manbaul Ulum boarding daughter Bata-Bata Pamekasan, and the role of housekeeper (nanny pesantren) in innovation in pesantren daughter. This study used descriptive qualitative approach. Techniques used in data collection interviews, observation and documentation. While analyzing the data using an inductive approach. Conclusion The research indicates that innovation efforts are made in modernizing schools daughter is using the principle of POAC (Planning, Organizing, Actuating, and Controlling) and time management. While the changes made in the education system using a selective integration model boarding school transformation.